Patterns and drivers of the global diversity of non‐native macrofungi - Monteiro, Miguel (2022)
Aim: To uncover the biogeography of non-native macrofungal diversity worldwide, by analysing patterns and drivers of (1) regional variation in species richness, (2) compositional similarity between regional species assemblages and (3) the spatiotemporal trends of first records. Location: Global. Methods: We used a database providing 1608 distribution records of 554 non-native macrofungal species in 167 national and sub-national regions worldwide. Regression models accounting for regional levels of recording capacity were used to relate spatial variation of non-native macrofungal richness and of regional compositional similarities to variables representing geographical, socio-economic and biophysical characteristics of regions. Temporal trends of first records were assessed at the global and continental scales and for distinct ecofunctional groups. Results: Regions reporting higher diversity of non-native species occur mainly in Europe, the Americas and Oceania. Regression models showed that regions with greater gross domestic product per capita, areal extent and in the Southern Hemisphere have higher non-native species richness, while regions with similar mean temperatures and latitudinal position share higher compositional similarities. Numbers of first records of non-native macrofungi have grown quasi-exponentially between 1753 and 2018, reflecting not only improved recording capacities but also likely an increasing number of introductions.Main Conclusions: We find that many regions of the world already harbour a high diversity of non-native macrofungi, with economic, climatic and introduction pathwayrelated factors explaining a relevant portion of the geographical patterns formed by these taxa. Given that socio-economic activity has increased strongly in recent decades, the global anthropogenic redistribution of macrofungi is likely to intensify further in the near future.